Deciphering CSU pathogenesis: Network toxicologyand molecular dynamics of DOTP exposure - Fang Cao; Cui Guo; Jing Guo (Ecotoxicology and Environmental Safety)
Objective: This study elucidated the molecular mechanisms underlying chronic spontaneous urticaria (CSU), potentially induced by the food and environmental pollutant dioctyl terephthalate (DOTP), through the application of network toxicology and molecular dynamics simulations. Methods: The structural analysis of DOTP was conducted in PubChem, with target prediction executed via Swiss Target Prediction and SuperPred, and target identification standardized using UniProt. A PPI network analysis identified core disease-related targets using STRING and Cytoscape. GO and KEGG analyses were utilized to explore target functions, particularly in inflammation and immune response pathways. AutoDock was employed for molecular docking to predict DOTP's binding to core targets, followed by molecular dynamics simulations with Gromacs to observe detailed interactions and conformational changes in the target proteins. Results: The study identified 38 potential targets associated with CSU and highlighted six core targets—EGFR, BCL2, NFKB1, CASP3, ERBB2, and mTOR—through PPI network analysis. GO and KEGG analyses illuminated the roles of these targets in biological processes, cellular components, molecular functions, and signaling pathways, with a particular emphasis on the PI3K-Akt signaling pathway. Molecular docking demonstrated strong binding affinities between DOTP and the core targets, while molecular dynamics simulations confirmed the stable binding of DOTP to these targets, with exceptional stability observed in its interaction with the mTOR protein. Conclusion: This study clarifies the potential molecular mechanisms of DOTP-induced CSU and underscores the efficacy of network toxicology, molecular docking, and molecular dynamics simulations in assessing the toxicity of food and environmental pollutants and their related molecular biological mechanisms. These findings offer new insights for future research, enhance our comprehension of the potential health impacts of food and environmental pollutants, and establish a scientific foundation for the development of prevention and treatment strategies.